Human Resource Management in Building an Organization Based on Innovation and Creativity - Harianto, Jakoep Ezra (Asian Journal of Multidisciplinary Research, 2024)
This article examines the role of human resource management (HR) in developing organizations that focus on innovation and creativity. In the midst of the challenges of the ever-changing business world, organizations are required to be able to adapt and produce creative solutions. For this reason, proper human resource management is very important to create an environment that supports innovation. The method used in this study is a qualitative approach through literature study or library research, with the aim of exploring how HR management can contribute to designing innovation-based organizational strategies. The findings of the study show that effective HR management includes the selection of employees who have creative potential, skill development through relevant training, and motivating rewards. In addition, visionary leadership and the ability to create an open and collaborative work culture also play an important role in encouraging the creation of innovative ideas. This study concludes that strategic and integrated HR management can be the main driver in creating highly competitive organizations through continuous innovation and creativity.